CO2MOVE Project: testing CO2 monitoring methods for onshore CCS - Melo, Clarissa Lovato; Goudinho, Flávio Soares; Bressan, Lia Weigert; Constant, Marcelo Jardim; Augustin, Adolpho Herbert; Iglesias, Rodrigo; Oliva, Andresa [UNESP]; Chang, Hung Kiang [UNESP]; do Rosário, Fátima; Musse, Ana Paula Santana (My University, 2018)
CO2 injection into geological reservoirs has been conducted for many years in Brazil as a method of Enhanced Oil Recovery, without the intention of geological storage. Recently, with pre-salt discoveries in ultra-deep waters and driven by the need to contain climate change, CO2 storage has become more relevant in the national energy production scenario. Therefore, one of the priorities in geological storage projects has been to demonstrate that CO2 is safely stored. This contributes to a better public perception of Carbon Capture and Storage (CCS) as a technological solution to reduce greenhouse gas (GHG) emissions in a short-term scenario. In Brazil, CO2 monitoring techniques and methodologies for onshore CCS purposes have been tested for 6 years supported by PETROBRAS in near-surface experiments with controlled CO2 releases. The first initiative in this sense started in 2012 with the Ressacada Project, in Florianópolis city (Santa Catarina state), and its activities are already closed. Since 2015 the CO2MOVE Project is under development in an area inside PUCRS campus, in Viamão city (Rio Grande do Sul state). This project involves more complex geological conditions and faces more challenges from the technological point of view. While in the Ressacada site prevailed quite sandy coastal marine sediments, the CO2MOVE site has a predominantly argillaceous soil, as a result of weathered granites. Local hydrogeology is characterized by a perched aquifer at about 1.5 meters depth, in which recharge depends on the local precipitation. CO2MOVE project is based on an automated injection system, capable of adding up to 50Kg of CO2 per day and a gaseous tracer injection module that allows incorporating tracers compounds to be tested as trackers of the injected CO2. Monitoring tools were arranged in an area of approximately 3000m2, occupying the entire region surrounding two vertical injection wells of 3 meters depth. Fieldwork involving injection and CO2 monitoring has been developed on two occasions. The first field season was conducted in 2016 for 60 days. The second campaign was conducted in 2017 for 15 days, aiming to obtain tracers response. This paper will present an overview of the CO2MOVE Project and the large experience acquired in these three years of research, approaching the behaviour of CO2 and tracers observed through the multiple research methods covered.
Keywords: carbon capture and storage; carbon isotope ratios; CO2 controlled release; CO2 monitoring; geoelectrical monitoring; perched aquifers; soil CO2 flux